Personal Taxation, Portfolio Choice, and the Effect of the Corporation Income Tax - Feldstein, Martin S.; Slemrod, Joel (Journal of Political Economy, 1980)
Extending the traditional treatment of the corporate tax to an economy with a progressive personal tax fundamentally changes the analysis. While the corporate tax system (CTS) does increase the total tax rate on corporate source income for some investors, the exclusion of retained earnings implies that the CTS lowers the tax rate for high-income investors. Analyzing such an economy requires replacing the traditional "equal-yield" equilibrium condition with a more general portfolio balance model. In this model, introducing a CTS can actually increase the corporate share of the capital stock even though the relative tax rate on corporate income rises.